2021
DOI: 10.1111/mcn.13200
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review on mothers' experiences of online breastfeeding peer support: Motivations, attributes and effects

Abstract: Information on the experiences surrounding online breastfeeding peer support among breastfeeding mothers and its effects on breastfeeding outcomes is growing yet to be synthesized. The aim of this review was to synthesize the evidence of mothers' experiences of online breastfeeding peer support. An integrative review was conducted. Five electronic databases were searched. Two reviewers independently screened the articles for inclusion. The inclusion criteria were (1) involved original data focusing on mothers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
2
15
0
2
Order By: Relevance
“…Previous research has highlighted different areas of similarity, such as being in a similar geographical location, culture, employment status, marital status, age, and recency of childbirth, as contributors to peer relationship building [ 23 , 27 ]. Having similar experiences, however, seems to be one important aspect for successful relationships identified by many studies (e.g., [ 23 , 37 , 40 ]). Research on similarity-attraction suggests that surface-level (e.g., age, ethnicity) and deep-level (e.g., attitude, values) have impact on quality of social relation with peers and program adherence behaviours [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has highlighted different areas of similarity, such as being in a similar geographical location, culture, employment status, marital status, age, and recency of childbirth, as contributors to peer relationship building [ 23 , 27 ]. Having similar experiences, however, seems to be one important aspect for successful relationships identified by many studies (e.g., [ 23 , 37 , 40 ]). Research on similarity-attraction suggests that surface-level (e.g., age, ethnicity) and deep-level (e.g., attitude, values) have impact on quality of social relation with peers and program adherence behaviours [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peers may also have personalities that are incompatible with the mother, and mothers may also feel inadequate if they make comparisons with their peer [ 36 ]. This feeling of inadequacy can lead to suboptimal levels of support and result in poorer outcomes for mothers [ 37 ]. Thus, central to the effectiveness of peer support is the extent to which it is functionally adaptive, and in some cases, even good intentions from others may produce undesirable consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Já, na busca de informações por pesquisas na internet, o conteúdo acessado partiu principalmente de canais administrados por profissionais da saúde. 23 Outra pesquisa realizada na cidade de Soledad de Graciano Sánchez, no México, que explorou as experiências e crenças sobre a amamentação exclusiva de mães que chegam a um hospital público para consulta nutricional, revelou que a troca de experiências com suas mães e avós proporciona maior conforto durante o processo de amamentação. E, embora as mulheres entrevistadas apontem que o profissional da saúde oferte informações durante os atendimentos, o mesmo não se mostra suficiente para sustentar a prática cotidiana, as dúvidas que surgem ao longo do aleitamento e a ansiedade diante de situações inéditas.…”
Section: (M13)unclassified
“…A recent integrated review has found that women tend to seek online breastfeeding support if they were isolated or do not receive sufficient professional support, and that online support could be an accessible and easily available channel for them to learn from others' experience [8]. Nevertheless, most studies on the topic to date have focused on the qualitative aspects of the online support experience [8], and there remains a lack of intervention studies on online peer support intervention. Moreover, existing data on whether online breastfeeding peer support could help improve breastfeeding outcome remain scarce and inconclusive [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most studies on the topic to date have focused on the qualitative aspects of the online support experience [8], and there remains a lack of intervention studies on online peer support intervention. Moreover, existing data on whether online breastfeeding peer support could help improve breastfeeding outcome remain scarce and inconclusive [8].…”
Section: Introductionmentioning
confidence: 99%